Comparison of Metacognitive Strategies Used by Individuals with ADHD in Online Instruction - Brown, Victoria (Journal of the American Academy of Special Education Professionals, 2010)
The purpose of this study was to identify barriers that students with attention deficit/ hyperactivity disorder (ADHD) experienced in a web-based course delivery model and to determine what accommodations and metacognitive strategies individuals used to compensate for those barriers. This case study compared interactions of two individuals identified with ADHD to three other individuals without ADHD as they participated in an online lesson. Interviews were also conducted to obtain the participants’ perceptions of how they prepared for class. The observations and interviews were analyzed to determine patterns of behavior. As a result of this study, an understanding of how two students with ADHD interacted with web-based instruction enhanced the understanding of how to use multimedia to support student learning in online environments.